Perlindungan Hukum Bank Kustodian Terhadap Investor Sebagai Lembaga Penunjang Pasar Modal (PPM) Di Indonesia Menurut Undang-Undang Nomor 8 Tahun 1995 Tentang Pasar Modal - Rahmiati Rahmiati (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2023)
This study aims to identify and explain who are the capital market supporting institutions and the custodian bank's responsibilities to investors in terms of capital market laws. The type of research used is normative legal research. Based on the results of research related to Who are the capital market supporting institutions according to Law Number 8 of 1995 concerning the Capital Market, it is regulated under the Capital Market Law Chapter VIII and Government Regulation No. 45 of 1995 Chapter X, PPPM has the following provisions: Capital Market Supporting Professionals (PPPM) consist of accountants, legal consultants, appraisers, and notaries. Regarding the responsibility of the custodian bank to investors in terms of the capital market law, the Custodian Bank based on the provisions of Article 46 of the Capital Market Law has placed the right on the investor to claim compensation if the custodian bank makes a mistake either by intention, negligence or carelessness. It is stated in the capital market law that there are several sanctions that are given to capital market violators as follows: administrative sanctions Article 102 (1) and criminal sanctions Article 103 (1). Keywords : Custodian Bank, Investor, Capital Market